1988
DOI: 10.1159/000185111
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Urinary Tract Infections in Postmenopausal Women

Abstract: Twelve postmenopausal women who experienced frequent urinary tract infections were found to have atrophic vaginitis. Four of them who were taking sulfonamide preparations chronically also had an interstitial nephritis manifest by decreasing glomerular filtration rate and eosinophiluria. Treatment consisted of a Betadine douche daily for 1 week, administration of an appropriate nonsulfonamide antibiotic, and institution of estrogen therapy to restore glycogen deposition in the vaginal epithelium and promote ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…This finding is consistent with other studies and may reflect a high incidence of colonization in postmenopausal women by Gramnegative coliforms bacteria of distal urethra and the introitus. 1,16 Catheter-associated UTIs comprise perhaps the largest institutional reservoir of nosocomial antibiotic-resistant pathogens, the most important of which are multidrug-resistant Enterobacteriacae other than E. coli, such as Klebsiella, Enterobacter, Proteus, and Citrobacter; Pseudomonas aeruginosa; Enterococci and staphylococci; and Candida spp. 17 In our study, we also found, as in Ackermann's study, a higher proportion of non-E. coli Gramnegative organisms in patients with chronic urethral catheters than in patients with no exposure to catheters.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies and may reflect a high incidence of colonization in postmenopausal women by Gramnegative coliforms bacteria of distal urethra and the introitus. 1,16 Catheter-associated UTIs comprise perhaps the largest institutional reservoir of nosocomial antibiotic-resistant pathogens, the most important of which are multidrug-resistant Enterobacteriacae other than E. coli, such as Klebsiella, Enterobacter, Proteus, and Citrobacter; Pseudomonas aeruginosa; Enterococci and staphylococci; and Candida spp. 17 In our study, we also found, as in Ackermann's study, a higher proportion of non-E. coli Gramnegative organisms in patients with chronic urethral catheters than in patients with no exposure to catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Larsen and colleagues 9 found that women on oestrogen therapy had larger numbers of vaginal lactobacilli compared to those not receiving this hormone who had a mixed aerobic and anaerobic¯ora. Privette and colleagues 18 studied urinary tract infection in postmenopausal women and found that the incidence was reduced by oestrogen therapy alone. These observations are insuf® cient, however, to provide a clear picture of the effect of HRT on the vaginal¯ora.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic treatments include estrogen in postmenopausal women (36,41,125,140,198,208,214) or cranberry juice (13,77,200), although the efficacy of the former remains controversial. Treatment of UPEC-infected mice with forskolin, a drug that increases intracellular cyclic AMP (cAMP) levels, expels UPEC from intracellular vesicles into the extracellular milieu, rendering the bacteria susceptible to immune responses and antibiotics (29).…”
Section: Weapons Systems: Current and Proposed Treatments And Vaccinementioning
confidence: 99%